Enzymatic construction of antibacterial ultrathin membranes for dyes removal - Wang, J.; Qin, L.; Lin, J.; Zhu, J.; Zhang, Y.; Liu, Jian; Van der Bruggen, B. (Elsevier BV, 2017)
© 2017 Elsevier B.V. This work is focused on the application of a novel antibacterial nanofiltration (NF) membrane formed by interfacial polymerization on a polyethersulfone supporting membrane for dye removal. Lysozyme, a ubiquitous and cheap enzyme with antibacterial activity was deployed as an aqueous monomer to react with 1,3,5-benzenetricarbonyl trichloride (TMC) to construct separation membranes. The formation of an ultrathin lysozyme-polymer active layer was verified by ATR-FTIR and FESEM. The degree of crosslinking, controlled by the concentration of lysozyme and TMC, had a significant influence on the physicochemical properties of the resultant membrane, as well as its separation performance. The optimum membranes show a high water flux (58.04 L m-2 h-1), distinguished rejection for low molecular weight reactive dyes (600–800 Da, >98.0%) and a high permeation of salts (>95%). Furthermore, the membranes with higher lysozyme concentration exhibited a sufficient antibacterial activity (81.9%) for E. coli bacteria. This facile strategy of enzyme immobilization not only allows for an in-situ preparation of enzyme-polymer membranes, but also maintains the native enzyme activity despite the high degree of covalent bonding between proteins. The resultant lysozyme membranes prove their potential in dyes removal, while also corroborating the value of interfacial polymerization in the field of enzyme immobilization and protein-polymer film construction.